Influence of features of information leakage channels on intelligibility of eavesdropped voice messages - Ликов, Юрій Володимирович; Морозова, Ганна Дмитрівна; Кукуш, Віталій Дмитрович (Technology audit and production reserves, 2017)
Speaking about speech information primarily it comes to negotiating, meetings and so on. In preparing the premises for such events we focus on assessing of possibility of speech acoustic information leakage through technical channels being the object of the study. Speech intelligibility is used as a quality criterion for acoustic channel of information leakage. During analyzing of information leakage in acoustic channels there are several features that impede using of well-known existing methods of intelligibility evaluation for estimation of channel protection. Such features are related to the couplings between eavesdropped speech and (a) level of channel-specific interferences or (b) semantic of a speech or (c) possibility to repeat a recorded message. The article presents results of investigations related to these features. The results of research (in graphs), which are shown in this article, the authors obtained experimentally. The obtained results improved the objectivity evaluating intelligibility of speech (and hence information security), as included the features of acoustic leakage channels, namely: takes into account the possibility of recording an acoustic signal and a further its repeated listening; takes into account fact that most often semantic speech is transmitted through the leakage channel; taken into account types of noise that are inherent office premises; takes into account imperfection of attacker’s equipment that can cause audio clipping. The results can be used as improvements of existing methodologies for estimation of information security hazards during analyzing of voice-channels, as well as for justification of requirements of appropriate technical means of information protection. It is established that to guarantee speech information security must be realized the signal/white noise is not over -20 dB.